Therapeutic effects of different intervention forms of human umbilical cord mesenchymal stem cells in the treatment of osteoarthritis - Zhang, Yuelong; Zhuang, Huangming; Ren, Xunshan; Jiang, Fuze; Zhou, Panghu (Frontiers in Cell and Developmental Biology, 2023)
Osteoarthritis (OA) is a common and disabling disease. For advanced OA, surgical treatment is still the main treatment. Human umbilical cord mesenchymal stem cells (hUC-MSCs) are self-regenerative pluripotent cells, that coordinate cartilage regeneration by secreting various trophic factors, which adjust the injured tissue environment. hUC-MSCs secret extracellular vesicles and participates in OA treatment by transmitting bioactive molecules related to migration, proliferation, apoptosis, inflammatory reaction, extracellular matrix synthesis and cartilage repair. In addition, the combination of multiple substances represented by cartilage matrix and hUC-MSCs also have a significant synergistic effect on OA treatment.Because hUC-MSCs have shown considerable promise in cartilage repair, some scholars have proposed transplanting mesenchymal stem cells into damaged cartilage to delay OA progression. This article reviews the application of hUC-MSCs as a treatment for OA. With the continuous development of routine clinical applications, more reliable intervention modalities for hUC-MSCs in OA treatment will be discovered for the time to come.